Pengelolaan Sarana dan Prasarana Pendidikan dalam Meningkatkan Mutu Pembelajaran Siswa di Madrasah Aliyah Darul Lughah Wal Karomah - Kurniana, Nela; Wahab, Abd Aziz; Badruddin, M. Fuad (Indonesian Journal of Islamic Educational Management, 2024)
Management of Educational Facilities and Infrastructure in Improving the Quality of Student Learning at Madrasah Aliyah Darul Lughah Wal Karomah". Many factors greatly influence the success of educational programs through the teaching process, one of which is the availability of adequate educational facilities and infrastructure as well as their optimal use and management. This research aims to find out the following things: management of facilities and infrastructure, obstacles to management of facilities and infrastructure, evaluation of management of facilities and infrastructure. This research uses a qualitative method with a descriptive approach. Data was collected through observation, interviews and data collection. The results of the research show the following: (1) Management of facilities and infrastructure begins with meetings held by all components of the madrasah, namely the head of the Madrasah, teachers and staff to obtain priority procurement of facilities and infrastructure and adjust them to existing funds. Then it will be recorded in the inventory book for a period of one year. (2) An obstacle to the management of infrastructure is where classrooms used for learning are also used for other activities. Students need to be aware of the use of infrastructure in the classroom so that it is not quickly lost or damaged. (3) evaluation of the management of infrastructure facilities which is carried out every year, every change made will have a positive impact so that the maintenance of the facilities can be maintained.